TNFRSF13B Diversification Fueled by B Cell Responses to Environmental Challenges—A Hypothesis - Cascalho, Marilia; Platt, Jeffrey L. (Frontiers in Immunology, 2021)
B cell differentiation and memory are controlled by the transmembrane activator and CAML interactor (TACI), a receptor encoded by TNFRSF13B. TNFRSF13B mutations are frequently found in common variable immunodeficiency (CVID) and in IgA -deficiency; yet, ~98% of those with mutant TNFRSF13B are healthy. Indeed, TNFRSF13B is among the 5% most polymorphic genes in man. Other mammals evidence polymorphism at comparable loci. We hypothesize that TNFRSF13B diversity might promote rather than detract from well-being. We shall discuss how extraordinary diversity of TNFRSF13B could have evolved and persisted across diverse species of mammals by controlling innate and adaptive B cell responses in apparently paradoxical ways.